Amino acid profile, peptide size distribution, antioxidant effect, and enzyme inhibitory activities of fava bean (Vicia fava) protein hydrolyzates - Timilehin David Oluwajuyitan; Deepak Kadam; Rotimi Emmanuel Aluko (International Journal of Food Properties)
The objective of this study was to determine the amino acid profile, peptide molecular size distribution, antioxidant effects, and enzyme inhibitory activity of fava bean protein hydrolyzates (FBPHs). The hydrolyzates were prepared using six proteases: alcalase hydrolyzate (ALCH), chymotrypsin hydrolyzate (CHYH), flavourzyme hydrolyzate (FAVH), pepsin hydrolyzate (PEPH), thermoase hydrolyzate (THEH), and trypsin hydrolyzate (TRYH). Results showed that FAVH and PEPH had significantly (p < .05) higher contents of histidine and proline, respectively. ALCH, FAVH, TRYH, and CHYH had narrower (0.19–4.9 kDa) peptide size distribution than PEPH (0.19–6.9 kDa) and THEH (0.19–11.3 kDa). FAVH had significantly (p < .05) stronger ability to scavenge superoxide and hydroxyl radicals as well as inhibition of linoleic acid peroxidation when compared to the other FBPHs. In addition, FAVH also showed the strongest (p < .05) inhibition of α-glucosidase, pancreatic lipase, and arginase activities. However, PEPH had the strongest (p < .05) inhibition of α-amylase and angiotensin-converting enzyme, while THEH inhibited renin activity the most. It is concluded that hydrolysis of fava bean protein with flavourzyme generated the most active peptide followed by pepsin hydrolysis. Therefore, FAVH and PEP could be used to produce peptides with functional properties against oxidative stress and associated degenerative diseases.